Assessment of the Aquino Pilot Decentralization Project - Brillantes, Alex B.; Cuaresma, Jocelyn C
The first Pilot Decentralization Project conducted in the provinces of Laguna, Tarlac, Negros Occidental and Davao Orintal is evaluated based on the following: (1) the extent of participation of beneficiary provinces in the decision making process of the project; (2) the extent of devolution of authority to the pilot provinces; and (3) the use of the block grants and the management of projects. The evaluation underscores the lack of specified representation for the pilot provinces in the Cabinet Action Committee on Pilot Decentralization; the lack of substantive authority and power devolved to the local government units; and the absence of specific implementing guidelines for the project. In view of these, th
Keywords: Aquino Pilot Decentralization Project (APDP); Local Government - Philippine; Decentralisation - Philippines